Valorizing meat by-products for human consumption: understanding consumer attitude formation processes - Lavranou, Georgia; Henchion, Maeve; McCarthy, Mary B.; O’Reilly, Seamus J. (Frontiers in Animal Science, 2023)
Introduction A considerable body of research has identified that meat by-products contain significant amounts of high-quality protein, which when properly extracted can lead to valuable opportunities for the food industry. However, the market success of food products containing protein extracted from meat byproducts is subject to consumer acceptance. This study explores Irish consumers’ attitudes toward hypothetical food products containing protein derived from beef offal sources. Methods A nationally representative survey (n = 953) was undertaken to investigate what attitude processes, that is intuitive and/or deliberative, dominate attitude formation toward food products containing beef offal-derived protein, while accounting for the effects of product familiarity and information provision. Using a 2 x 3 between-subject design, study participants were randomly assigned to one of the 6 study conditions. Participants were exposed to Affect Misattribution Procedure (AMP) tasks which measured their intuitive evaluations, followed by a number of questions that measured deliberative evaluation, attitude ambivalence, attitudes and acceptability toward the food products containing protein extracted from beef offal. Results The study reveals that consumers’ intuitive and deliberative evaluations worked in the same direction, predicting overall attitudes toward these products; however, deliberative evaluation was found to be a better predictor of consumers’ attitudesthan intuitive evaluation. Moreover, intuitive evaluations do not influence deliberative evaluations, suggesting that information provision that prompts deliberative evaluations could lead to the formation of more considered and stable attitudes. Familiarity influences acceptance: these findings suggest that the potential impact of a lack of familiarity with the ingredient is offset by familiarity with the carrier products. Consumers who received benefit information about the health and environmental consequences of consuming food products containing protein extracted from beef offal expressed a more positive deliberative attitude toward these products. However, interestingly, the provision of benefit- and risk-orientated information at the same time at the same time also had a positive effect on deliberative evaluations. Discussion The findings have implications for new product development, and more generally for strategies that seek to promote sustainable food production and consumption.